Komik Digital Warak Ngendog Sebagai Alternatif Media Pembelajaran Keragaman Budaya Pelajaran IPAS Di Kelas IV Sekolah Dasar: Analisis Antropologi Pendidikan - Fidiyaningrum, Anis (Pena Edukasia, 2024)
With the development of technology, children are more interested in foreign cultures, such as K-Pop, online games, and so on. Children's knowledge about the cultures in Indonesia, especially those in Semarang City, is decreasing, and some even don't know about them. This is not in line with the government's expectation that every Indonesian citizen should know and understand their own culture. The research method used literature studies from several scientific journals. Warak Ngendog digital comic is an alternative learning media that can be used by elementary school teachers, especially grade 4 in IPAS lessons with cultural diversity material. Through Warak Ngendog digital comics, there are cultural values, moral values, and skill values that can help children's social development and motor, affective and cognitive intelligence. By utilizing the current development of science and technology, digital comic media can be transformed into a modern form of learning media while maintaining its traditional cultural values.